Facebook Usage In Learning English Writing Skill And In Improving Students’ Motivation - Rahman, Abdur; Anita Aulia, Ersa (Lembaga Penelitian dan Pendidikan Mandala, 2024)
One of the applications of information technology used to this research is Facebook. It is very most famous and there are many students use it. Therefore, Facebook is used as a learning media for English writing skill in the schools. Many teachers found that most the students used Facebook in class. They ignore to study and only focus on Facebook. This research is to find the influence of Facebook on learning English and students’ motivation in writing skill. Therefore, using Facebook as a learning tool for students is investigated with the title